Joint Associations of Accelerometer-Measured Physical Activity and Sedentary Time with Body Mass Index: Cross-Sectional Evidence from the Latin American Study of Nutrition and Health - De Moraes-Ferrari, G (Elsevier Ltd, 2025)
Background: More research is required to determine the joint associations of physical activity and sedentary time with body mass index (BMI) in Latin America. Therefore, the objective of the present study was to investigate said associations in eight countries in the region. Methods: Physical activity and sedentary time were measured using accelerometers in 2404 participants aged 39.30 ± 12.93 years who took part in the Latin American Study of Nutrition and Health. Linear regression was used to investigate associations with BMI and logistic regression was used to investigate associations with obesity. Results: The average BMI was 27.51 ± 5.35 kg/m2. Physical activity was inversely associated with BMI, such that every 30 min/day was associated with a BMI 3.75 kg/m2 lower. Compared to the group with high physical activity and low sedentary time, the odds ratio for obesity was no greater in the group with high physical activity and high sedentary time [0.70 (0.45,1.09)]. The risk was greater in the group with low physical activity and low sedentary time, although the confidence interval was relatively wide and included the value of 1.00 [1.36 (0.92,1.80)]. The risk was greater in the group with low physical activity and high sedentary time [1.71 (1.21,2.41)]. Conclusions: Weight loss is incredibly difficult at the population level and primary prevention may be more effective in countries where obesity is still emerging as a major health issue. This study suggests that physical activity may have a more important role than sedentary time in the primary prevention of obesity in Latin America. Trial registration: ClinicalTrials.Gov NCT02226627. Retrospectively registered on August 27, 2014. © 2025 Asia Oceania Association for the Study of Obesity